Monitoring the impact of COVID-19 in Myanmar: Mechanization service providers - November 2020 survey round - Takeshima, Hiroyuki; Zone, Phoo Pye; Masias, Ian (International Food Policy Research Institute, 2020)
Mechanization service providers (MSP) in Myanmar were originally surveyed by telephone over three rounds in May, June, and July 2020 to determine how their businesses were being affected by COVID-19 related restrictions. Most of the MSPs interviewed were engaged in providing farmers with tractor-related services. The results of those surveys were published in Myanmar Strategy Support Program Policy Notes 07, 12, and 17, respectively. To trace the continuing impact of the COVID-19 pandemic on their economic activities, a fourth round of the survey of MSPs was done in early-November 2020, administered mostly to those engaged in harvesting activities. This note reports on the results of the fourth survey, as well as some trends seen between the earlier survey rounds and this last one.